Caregiving burden, depression, and anxiety in informal caregivers of people with mental illness in China: a cross-sectional survey - Hao Yao; Kunmei Li; Chuan Li; Shuang Hu; Zhuoer Huang; Jianhua Chen; Yifeng Xu (BMC Psychiatry)
Abstract Background Caregiving for people with mental illness (PwMI) could be burdensome, especially for informal caregivers. However, there is a scarcity of research investigating caregiving burden among informal caregivers of PwMI in China at the national level. To fill this gap, this study examined the prevalence of caregiving burden, depression, and anxiety, as well as their associated factors, among a cross-sectional sample of informal caregivers of PwMI in China. Methods Data were collected via an online survey between June and November 2023. Caregiving burden, depression, and anxiety were measured by the Zarit Burden Interview, the Patient Health Questionnaire, and the Generalized Anxiety Disorder Scale. Information on caregivers’ sociodemographic, care recipients’ sociodemographic and disease-related, and caregiving-related characteristics was also collected. Hierarchical regression analyses were performed to identify associated factors of caregiving burden, depression, and anxiety. Results A total of 1,224 informal caregivers of PwMI in China were included in the final analysis. 72.1% of the participants had high caregiving burden, 53.5% had moderate to severe depression, and 43.1% had moderate to severe anxiety. Caregiving burden, depression, and anxiety were inter-correlated with each other but exhibited different profiles of associated factors. The most important factors associated with all the three outcomes were disease-related characteristics, particularly care recipients’ symptom stability, medication compliance, and insight. Informal caregivers of males with mental illness had higher levels of caregiving burden, depression, and anxiety than those of females. There was a lack of differentiation in caregiving burden, depression, and anxiety based on care recipients’ diagnosis. Formal or common-law marriage was a protective factor for caregiver depression and anxiety but not for caregiving burden. Conclusion Informal caregivers of PwMI in China experienced a high level of caregiving burden, depression, and anxiety. Urgent actions are needed to relieve caregiving burden, depression, and anxiety among informal caregivers of PwMI in China.